(3OYhI GdCWHGAs - (3GHf HWdGf , GdeNJGQ Hf GdMSf Hf YHOhf, CHh GdMSf,J (B458 (3g` s ((3eMeO Hf bjUQ GdEScfOQi s)
(3ChdgG (B:s
(3OYhI GdCWHGA Ydi ePgH UGMH cdjdI hOefI , jTJed Ydi eRL jHSf Yf LO , hHGWd jfWb Yf Mb s
(3BNQgG (B:s
(3MjK dG jJYPQ eWdhH , hdG jabO eMHhH , HJjSjQ hQVG bdH Sdje , Efg LhGO eLjO bQjH eLjH s
(3GdfSNI HgG MhGTs
(3bGd GdbaWis
(3OYhI GdCWHGA ebGeI XQjaI (B" (3UfagG GdeNJGQ Hf GdMSf ddCejQ fUQ GdOhdI CHj fUQ CMeO Hf eQhGf fSNI ePgHI GdWGdYs
(3JTed Ydi QSeGdgG ddCTNGU ai GhVGY eNJdag s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdWHs